The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1016/j.ejrnm.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The many, atypical presentations of musculoskeletal hepatocellular carcinoma (HCC) metastases

Abstract: Purpose: To demonstrate many uncommon, non-classical clinical presentations of HCC that have been gathered from an endemic region in the Nile Basin. Patients and methods: We will highlight cases of high quality MDCT performed for various clinical symptoms not classically associated with advanced or metastatic HCC and the role of image-guided biopsy in diagnoses. These include: (a) gradual progressive weakness of lower limbs; (b) Retrosternal pain not responding to medications; (c) severe right hip pain; (d) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…There were 41 studies reported unusual presentation of hepatocellular carcinoma and metastasis; 36 studies were case reports, single case series from Egypt (372), two cohort studies from Egypt (373), two cross sectional studies ; one from Algeria and another from Tunisia.…”
Section: Case Control Studiesmentioning
confidence: 99%
“…There were 41 studies reported unusual presentation of hepatocellular carcinoma and metastasis; 36 studies were case reports, single case series from Egypt (372), two cohort studies from Egypt (373), two cross sectional studies ; one from Algeria and another from Tunisia.…”
Section: Case Control Studiesmentioning
confidence: 99%